Pandangan Hukum Ekonomi Syariah Tentang Makanan Tanpa Ada Batasan, (All You Can Eat ) - Mariani Ginah; Raudhatul Janah; Fahrisina Rafiqah; M. Luthfi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research explains the buying and selling of food with the All You Can Eat concept and is explained from the perspective of Sharia economic law. This buying and selling is done to attract buyers or visitors to take part in a tradition that has existed for a long time but is currently developing again and is being born in a modern way, namely the tradition of food being served in a buffet style so that now many people are following a trend called All you can eat. Basically this is a marketing strategy. The writing method used is using library research and qualitative field research, namely participating as a buyer when making a transaction using the All you can eat concept.